Pharmacological modulation of immunoreactive imidazoline receptor proteins in rat brain: relationship with non-adrenoceptor [3H]-idazoxan binding sites. - Escribá, P. V. (1996)
1. The densities of various imidazoline receptor proteins (with apparent molecular masses of approximately 29/30-45- and 66-kDa) were quantitated by immunoblotting in the rat cerebral cortex after various drug treatments. The modulation of these imidazoline receptor proteins was then compared with the changes in the density of non-adrenoceptor [3H]-idazoxan binding sites (I2-sites) induced by the same drug treatments. 2. Chronic treatment (7 days) with the I2-selective imidazol(in)e drugs idazoxan (10 mg kg-1), cirazoline (1 mg kg-1) and LSL 60101 (10 mg kg-1) differentially increased the immunoreactivity of imidazoline receptor proteins. The levels of the 29/30-kDa protein were increased by idazoxan and LSL 60101 (23%), the levels of the 45-kDa protein only by cirazoline (44%) and those of the 66-kDa protein only by idazoxan (50%). These drug treatments also increased the density of I2-sites (32-42%). 3. Chronic treatment (7 days) with efaroxan (10 mg kg-1), RX821002 (10 mg kg-1) and yohimbine (10 mg kg-1), which possess very low affinity for I2-imidazoline receptors, did not alter either the immunoreactivity of imidazoline receptor proteins or the density of I2-sites. 4. Chronic treatment (7 days) with the monoamine oxidase (MAO) inhibitors clorgyline (10 mg kg-1) and phenelzine (10 mg kg-1) decreased the immunoreactivity of the 29/30-kDa (17-24%), 45-kDa (19%) and 66-kDa (23-31%) imidazoline receptor proteins. The alkylating agent N-ethoxycarbonyl-2-ethoxy-1, 2-dihydroquinoline (1.6 mg kg-1, 6 h) also decreased the levels of the three imidazoline receptor proteins (20-47%). These drug treatments consistently decreased the density of I2-sites (31-57%). 5. Significant correlations were found when the mean percentage changes in immunoreactivity of imidazoline receptor proteins were related to the mean percentage changes in the density of I2-sites after the various drug treatments (r = 0.92 for the 29/30-kDa protein, r = 0.69 for the 45-kDa protein and r = 0.75 for the 66-kDa protein). 6. In the rat cerebral cortex the I2-imidazoline receptor labelled by [3H]-idazoxan is heterogeneous in nature and the related imidazoline receptor proteins (29/30-, 45- and 66-kDa) detected by immunoblotting contribute differentially to the modulation of I2-sites after drug treatment.